Enhancing Business Motivation: Exploring the Impact of Spiritual and Emotional Intelligence in Organizational Contexts - Muslinawati, Retno; Azhari, Azhari; Bachtiyar, Achmad Akbar Agym; Alfiyana, Siti (Universitas Bumigora, 2024)
In this increasingly rapid business competition, business motivation is important to improve the quality of business performance. This is also one way to increase the company's internal strength. This research aims to determine the influence of spiritual and emotional intelligence on business motivation. The method used in this research is a quantitative method, with descriptive associative analysis. The respondents of this research are the people of Bojonegoro Regency. The sampling technique is based on a representative sample size, which in this case is 50 samples. Data analysis was carried out in several stages, namely testing the validity and reliability of research instruments, classical assumptions’ test, and hypothesis test. The results of this study show that spiritual intelligence and emotional intelligence have a significant and positive effect on business motivation, and they simultaneously have a positive effect on business motivation. Thus it can be explained that improving spiritual and emotional intelligence appears as a critical method for fostering business motivation in more competitive situations, hence strengthening internal organizational resilience. The findings contribute in providing useful insights for companies seeking to nurture a motivated workforce by stressing the development of spiritual and emotional intelligence in employees. This technique not only improves individual performance, but it also strengthens the organization's overall ability to prosper in adverse market conditions.